2004
DOI: 10.1007/s11661-004-0367-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of strain accumulation and damage development during creep of prestrained 316 stainless steels

Abstract: The effects of prestraining at room temperature and at the creep temperature of 848 K, as well as the responses to stress reductions during creep, have been studied for 316 stainless steels varying in composition and initial microstructure. The results are analyzed by contrasting the strengthening effects achieved by introducing high dislocation densities prior to creep exposure with the deleterious effects, which can occur when prestraining causes premature void nucleation at grain boundaries. In addition, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 16 publications
7
30
0
Order By: Relevance
“…Wilshire and Willis also reported the effects of high temperature pre-straining on the subsequent creep behaviour of 316L stainless steel at 575 • C by reducing the test stress after an initial stage. Immediately after the load reduction, the creep rate became extremely low and, after that, it increased to a value similar to the minimum creep strain rate observed during a constant stress creep test [31]. The behaviour of 316 stainless steel was also investigated by Hyde who reported the results of plasticity/creep tests performed at 550 • C by applying a creep load to the specimens and overloading for 3 sec at regular time intervals of 168 h [33,34].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Wilshire and Willis also reported the effects of high temperature pre-straining on the subsequent creep behaviour of 316L stainless steel at 575 • C by reducing the test stress after an initial stage. Immediately after the load reduction, the creep rate became extremely low and, after that, it increased to a value similar to the minimum creep strain rate observed during a constant stress creep test [31]. The behaviour of 316 stainless steel was also investigated by Hyde who reported the results of plasticity/creep tests performed at 550 • C by applying a creep load to the specimens and overloading for 3 sec at regular time intervals of 168 h [33,34].…”
Section: Introductionmentioning
confidence: 88%
“…• C [30,31]. A drastic reduction in the creep ductility and the minimum creep rate was observed for both PST and FST 316 stainless steels, while the failure time was found to decrease for the PST material and to increase for the FST material.…”
Section: Introductionmentioning
confidence: 95%
“…The phenomenon that creep deformation can be impeded by prestrain has been widely reported for engineering steels (see, e.g., [2,[4][5][6]). By employing thin-wall tubes of 316H stainless steel as creep test specimens (outside diameter, wall thickness and gauge length are 21 mm, 1 mm and 70 mm, respectively), Ohashi et al [4] examined the effect of pre-tension on subsequent creep at elevated temperature (650…”
Section: Creep Resistance Effectsmentioning
confidence: 99%
“…Yet, because high temperature creep, as a complex multi-physics-coupled phenomenon, is sensitive to many factors, e.g., material composition and microstructure, operating conditions (temperature and stress level) and sample geometry, several seemingly conflicting outcomes of prior deformation have been reported. For example, Wilshire and Willis [2] found that prestrain at room temperature for 316H/L stainless steel can increase creep resistance; Zhang and Knowles [3] showed a contrary effect for nickel base C263 superalloy where prestrain reduces creep resistance. Thus, the purpose of this work is to review published studies in the field of prior-deformation effects on subsequent high temperature creep for metallic materials to gain an overall understanding of this topic.…”
Section: Introductionmentioning
confidence: 99%
“…In a uniaxial creep test, damage occurs only in the tertiary creep region [35][36][37], while during a small punch creep test the material is subjected to damage in both the primary and secondary regions of the creep curve as well as in the tertiary region [20,24]. Damage can be described as the ratio between the damaged area and the initial area.…”
Section: Creep Damage Materials Modelmentioning
confidence: 99%